Creditor Protection in Individual Company Bankruptcy - Asy’arie, Moh. Asadullah Hasan Al; Wibowo, Benedictus Satryo; Rahmanda, Bagus; Irawati, Irawati (International Journal of Business, Law, and Education, 2025)
This study examines the legal and financial implications of Indonesia’s recognition of sole proprietorships as a new legal entity under the Job Creation Law for micro, small, and medium enterprises (MSMEs). While this status facilitates business establishment and access to funding, it raises risks for creditor protection due to weak legal and financial safeguards. Using a non-doctrinal, empirical juridical approach through interviews and legal analysis, the research identifies key challenges: MSME actors’ limited legal awareness, creditors’ restricted access to financial information, poor separation of personal and business assets, and inefficiencies in the judicial system. These conditions heighten creditor vulnerability in cases of insolvency. The study recommends strengthening regulations, improving legal education for MSMEs, enhancing financial transparency, and empowering relevant institutions to ensure fairer creditor protection and a more sustainable business climate, particularly in Labuan Bajo.